Switched capacitor based multi-level boost inverter for smart grid applications - Mostafa Al gabalawy; Ramy M. Hossam; Shimaa A. Hussien; Nesreen S. Hosny (International Journal of Electrical and Computer Engineering (IJECE), 2021)
To link DC power sources to an AC grid, converters are needed. Inverters are the power electronic devices, which are used for this purpose. Conventional inverters employ harmonic filters and transformers that are lossy and expensive. Multilevel inverters (MLIs) are an alternative to conventional ones, proposing reduced total harmonic distortion (THD), increased range of control, and inductor-less design. They generate a stepped waveform, with close similarity to a sine wave. Many distributed sources may be employed in a smart grid. If those sources have minimal THD, the filtering process could be reduced at the point of common coupling. This paper presents two switched capacitor based MLIs, proposing boost capability and low THD. Inverters have inherent charge balancing capability, which eliminates the need for auxiliary circuits and voltage sensors. Inverters switches are modulated using phase opposition disposition pulse-width modulation (PODPWM) method that ease the balancing of the voltage and decrease the losses of switching. Designs were verified by simulation and the output waveforms were introduced.